Comparação de variáveis limnológicas em dois reservatórios do rio Jacuí no Rio Grande do Sul - Prado, Diego de Almeida (2014)
In view of the great potential of using remote sensing coupled with studies of aquatic environments, the focus of this Master Dissertation refers to the analysis of two watershed and influence of limnological variables in their respective reservoirs, located in the central region of state of Rio Grande do Sul. From this perspective, the general objective of this research is to compare the dynamics of limnological variables of reservoirs Itaúba and Dona Francisca, located on the upper course of the Jacuí River, in the context of their hydrographic basins. The study, carried out in the catchment basins of the two reservoirs, enabled emphasizing the physical and environmental conditions and interrelationships with the use of remote sensing images and limnological data. The study was conducted according to the following steps: data gathering, development of cartographic base, quantification and analysis of data and finally the writing of the paper. The results of this study help us check the main agricultural activities, which are characterized by the cultivation of soybeans and corn in the summer season, and the planting pastures such as wheat, ryegrass and wild radish in early winter. The rainfall data showed some irregularity in the volume of accumulated rainfall in the two areas in question. The analysis of limnological data is related to many other factors, including the different land uses of the hydrographic basin and rainfall when they relate to the increase of suspended sediment and other materials. In the comparison of the temperatures of the tanks, it was observed that the reservoir of Dona Francisca showed the greatest amplitude. This demonstrates the reservoir Itaúba showed smaller variance in temperature in relation to the other reservoir. Comparing the averages of transparency of water in the reservoirs, it was observed that the reservoir Dona Francisca showed the smallest variation between the observed values. This shows that this reservoir showed less variance of transparency in relation to the other reservoir. Comparing the values of total suspended solids (TSS) of the reservoirs, it was observed that the reservoir Itaúba showed the lowest variation. In a comparison between the two reservoirs it was observed that only the TSS variable showed significant difference. This indicates that the different weather and land using conditions provided significant differences in these reservoirs only in relation to suspended solids and they did not impact differently to temperature and water transparency.